Literasi Keuangan, Lifestyle Hedonism Terhadap Perilaku Keuangan Mahasiswa - Widyaningsih, Ika Utami (FEB Universitas Sultan Ageng Tirtayasa, 2024)
The aims of this research is to analyze the influence of financial literacy and lifestyle-hedonism on student financial behavior. This quantitative research took a sample of UNTIRTA’s Faculty of Economics and Business students. Students were used as sample considering that they are tendency to behave according to follow the trends. The samping technique used purposive sampling and obtained a total of 120 respondents. Data analysis uses validity and reliability tests, classical assumption tests and multiple linear regression tests. The result show that the greater understanding of financial literacy followed the greater financial management behavior of students. Increasing lifestyle-hedonism will also be followed by increasing financial behavior, especially in terms of controlling the use of money.